Environmental DNA Epigenetics Accurately Predicts the Age of Cultured Fish Larvae - Eliot Ruiz; Fabien Leprieur; Gérard Sposito; Martina Lüthi; Michel Schmidlin; Jacques Panfili; Loïc Pellissier; Camille Albouy (Ecology and Evolution)
ABSTRACT While acquiring age information is crucial for efficient stock management and biodiversity conservation, traditional aging methods fail to offer a universal, non‐invasive, and precise way of estimating a wild animal's age. DNA methylation from tissue DNA (tDNA) was recently proposed as a method to overcome these issues and showed more accurate results than telomere‐length‐based age assessments. Here, we used environmental DNA (eDNA) for the first time as a template for age estimation, focusing on the larval phase (10–24 days post‐hatch) of cultured Dicentrarchus labrax (seabass), a species of major economic and conservation interest. Using third‐generation sequencing, we were able to directly detect various modification types (e.g., cytosine and adenosine methylation in all contexts) across the whole genome using amplification‐free nanopore sequencing. However, aging sites were only present in the mitogenome, which could be a specific feature of eDNA methylation or the consequence of better DNA protection within mitochondria. By considering qualitative and quantitative information about aging sites according to an objective model selection framework, our epigenetic clock reached a cross‐validated accuracy of 2.6 days (Median Absolute Error). Such performances are higher than those of previous clocks, notably for adult seabass even when scaling MAE to the age range, which could be linked to a more dynamic epigenome during early life stages. Overall, our pilot study proposes new methods to determine the potential of eDNA for simultaneous age and biodiversity assessments, although robust validation of our preliminary results along with methodological developments are needed before field applications can be envisaged.